2011
DOI: 10.1039/c1sm00010a
|View full text |Cite
|
Sign up to set email alerts
|

Fast responsive and morphologically robust thermo-responsive hydrogel nanofibres from poly(N-isopropylacrylamide) and POSS crosslinker

Abstract: Stable thermo-responsive hydrogel nanofibres have been prepared by electrospinning of commercial poly(N-isopropylacrylamide) (PNIPAM) in the presence of a polyhedral oligomeric silsesquioxane (POSS) possessing eight epoxide groups and of an organic-base catalyst, followed by a heat curing treatment. The nanofibres showed excellent hydrogel characteristics with fast swelling and de-swelling responses triggered by temperature changes. They were also morphologically robust as their physical integrity was preserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 35 publications
2
77
1
Order By: Relevance
“…Electrospun nanofibrous mat with high porosity and adequate interconnecting pores can render water to access the whole matrix of hydrogel rapidly. Moreover, the small diameter of nanofibers also increases the mass exchanges inside the fibers to achieve fast response when external environment varies [13]. Nevertheless, it has never been reported that hydrogel is manufactured by electrospinning using PASP.…”
Section: Introductionmentioning
confidence: 97%
“…Electrospun nanofibrous mat with high porosity and adequate interconnecting pores can render water to access the whole matrix of hydrogel rapidly. Moreover, the small diameter of nanofibers also increases the mass exchanges inside the fibers to achieve fast response when external environment varies [13]. Nevertheless, it has never been reported that hydrogel is manufactured by electrospinning using PASP.…”
Section: Introductionmentioning
confidence: 97%
“…The PNH 5 and PNH 10 NFs responded quickly to changes in temperature, and their swelling ratio recovered within each cycle. In general, the application of bulk materials such as hydrogels is limited by their slow response, and several techniques have been proposed to increase the rate of response, such as reducing the gel size and constructing an interconnected pore structure within the gel [53]. Because of the high specific surface area of NFs, they are more sensitive to external stimuli than the corresponding bulk materials.…”
Section: Swelling and Shrinking Of The Crosslinked Nanofibersmentioning
confidence: 99%
“…Thus, for aiding the spinning process and enhancing the quality of the fibers, researchers have attempted to produce blends of PNIPAAm with other polymers, or coaxial nanofibers with PNIPAAm as core and other polymers as sheath. [26][27] Previous reports showed that PNIPAAm and poly(L-lactide) (PLLA) mixture with tunable surface morphologies can be increased by spinning from N-N-dimethylformamide (DMF). [28] Ethyl cellulose (EC) is a kind of polysaccharides with a good film-forming ability, hydrophobicity and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%